2017
DOI: 10.4209/aaqr.2016.10.0443
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Multi-Year Record of Size-Resolved Hygroscopicity Measurements from a Rural Site in the U.S.

Abstract: Hygroscopic growth factor (GF) distributions of 13, 25, 50, 100, 200, and 400 nm particles measured with a Hygroscopic Tandem Differential Mobility Analyzer (HTDMA) from 2009 to 2012 at the Southern Great Plains (SGP) site in Oklahoma, U.S. were used to describe time of day-and annually-averaged hygroscopicity parameters (κ). A diel pattern was often observed with an average daytime κ that was higher than that at other times, especially on days with new particle formation (NPF) events. The average hygroscopici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…S2, the average GF of 110 nm and 165 nm particles showed a clear diurnal pattern, which peaked at about 11:00 every day and reached a minimum at 20:00. This trend was similar to the GF observation in Po Valley (Bialek et al, 2014) or Oklahoma site (Mahish and Collins, 2017) and is often attributed to a shallower and more stagnant boundary layer during the night with temperature inversions arising from radiative cooling of the surface.…”
Section: Continental Air Massessupporting
confidence: 83%
“…S2, the average GF of 110 nm and 165 nm particles showed a clear diurnal pattern, which peaked at about 11:00 every day and reached a minimum at 20:00. This trend was similar to the GF observation in Po Valley (Bialek et al, 2014) or Oklahoma site (Mahish and Collins, 2017) and is often attributed to a shallower and more stagnant boundary layer during the night with temperature inversions arising from radiative cooling of the surface.…”
Section: Continental Air Massessupporting
confidence: 83%
“…The relationship between GF org and the organic oxidisation level is under intensive debate. In some studies, the GF org has been found to increase with an increasing O : C ratio in both chamber and ambient studies (Jimenez et al, 2009;Lambe et al, 2011;Massoli et al, 2010;Wong et al, 2011;Wu et al, 2016), and theoretical calculations have also demonstrated that GF org exhibits a linear dependence on the O : C ratio (Nakao, 2017). However, the correlation between GF org and the O : C ratio varies among aerosol sources, and some studies have reported no significant relationship (Chang et al, 2010;Suda et al, 2014).…”
Section: Closure Uncertainty and Error Analysismentioning
confidence: 99%
“…Therefore, the aerosol loading in this case was greatly influenced by biomass burning aerosols transported to the SGP site. Based on the analysis of a multi‐year record of hygroscopic measurements made at the SGP site (Mahish & Collins, ), a simplified hygroscopicity parameter κ equal to 0.2 is chosen for CCN retrievals here. This value falls within the reasonable range of κ for biomass burning aerosols (Petters et al, ).…”
Section: A Real Case Studymentioning
confidence: 99%
“…Although the SGP site is located in a rural area surrounded by cattle pastures and agricultural fields, air masses transported from the south and southeast often arrive at this site in the summer (Mahish & Collins, ). Based on an overview of aerosol‐type‐dependent properties from more than 10 years of lidar observations (Baars et al, ) and Figure , we can infer that aerosols in this case are not dust but urban or biomass burning aerosols by virtue of the lidar ratio (Figure a), the depolarization ratio (Figure b), and the Ångstrӧm exponent (Figure c).…”
Section: A Real Case Studymentioning
confidence: 99%